Iqra' learning courseware - Rosfarahin, Roslan (2011)
IQRA'Learning Courseware is a system that is aimed for people that interested in learning IQRA'.Nowadays,people usually use books in order to learn IQRA'.With this system, people no longer have to use the IQRA' book because it contains all the content in IQRA' book.This system deals with a number of useful functions where user may learn the basic word, the IQRA'and go through some exercises. There are two objectives of this courseware which are to teach the IQRA'learners more efficiently,in terms of time and the needs for instructors and also to computerized the IQRA' learning process. Rapid Application Development (RAD) is the methodology chosen for the development of this courseware as it requires shorter time to deliver the product. For the techniques, this courseware applied HCI technique which is Schneiderman's Eight Golden Rules of Interface Design in the courseware design. IQRA' Learning Courseware is expected to teach the IQRA' users effectively and efficiently. This report will discuss on the preparation and analysis that been collected throughout the development cycle of this system.